El rol de la familia para potenciar el desarrollo de la educación sexual infantil de los niños de primer grado de educación general básica paralelo c sección matutina de la escuela teniente Hugo Ortiz, de la ciudad de Loja, período 2017-2018. - Vega Condolo, Johanna Adelayda (2018)
This investigation is named the family roll for potency the development of the child sexual education of first grade basic general education class “C” ,morning section of Teniente Hugo Ortiz School, of Loja city period 2017-2018, it has as general objective determine the family roll for potency the development of the child sexual education. The methods that were used in the investigation were: scientific, analytic-synthetic, inductive, deductive and statistical method; in order to get the information were used different kind of techniques like: surveys to teachers and parents, observation and estimation scale applied to 22 children, were it could be verify that 81,81% of children show astonishment when they hear about their genitals, it is relates to the parameter that alludes, if the parents talk about sexuality with their children, later it is carry out the development of the activities for potency the child sexual education, it has a duration of eight weeks. In order to check the results before and after the execution of the approach, one more time the estimation scale was applied and it was obtained that 90, 91% of the children do not shows astonishment when they hear about their private parts, in relation to this positives results; finally it concludes that one of the implement that provides strategies to work in child sexual education was the workshop programming to the parents with the principal function is provide truthful and reliable information based on a search a social and personal wellness, it recommends to the parents inquire with current investigations about child sexuality in order to educate, guide and teach aspects like propose safety rules for their bodies, in such a way it serves as a prevention implement in face of the child abuse of their children, being that the parents are the principal personages in a children’s life and in this way potency the development and stimulation of these.